T Lymphocyte Predominance in Lesions of Canine Coccidioidomycosis - Shubitz, Lisa F. (Vet Pathol, 2010)
Coccidioidomycosis is a systemic fungal infection endemic to the southwestern United States. Although cell-mediated immunity is considered critical in control of the infection, little is known of the cellular population in naturally occurring lesions. To characterize the lymphocytic infiltration, archived formalin-fixed, paraffin-embedded tissues (subcutis, pericardium/heart, lung, bone, and synovium) from 18 dogs with coccidioidomycosis were studied with immunohistochemistry for CD3 and CD79a. In nearly all lesions, T lymphocytes were more numerous than B lymphocytes and were distributed throughout the lesion with concentration in the periphery of granulomas, whereas B lymphocytes were mostly confined to the periphery of granulomas. The predominance of T lymphocytes in lesions of canine coccidioidomycosis was independent of the tissue evaluated, the number of intralesional organisms, and the nature or severity of the inflammatory response.